2022
DOI: 10.1002/cmdc.202100732
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Derivatives Target the KEAP1/NRF2 Axis and Possess Potent Anti‐SARS‐CoV‐2 Activity

Abstract: Naturally occurring compounds represent a vast pool of pharmacologically active entities. One of such compounds is andrographolide, which is endowed with many beneficial properties, including the activity against severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2). To initiate a drug repurposing or hit optimization campaign, it is imperative to unravel the primary mechanism(s) of the antiviral action of andrographolide. Here, we showed by means of a reporter gene assay that andrographolide exerts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…For example, NRF2 activator SFN (phytochemical sulforaphane) has been reported to exhibit in vitro and in vivo antiviral activity against SARS-CoV-2 [ 59 ]. Some natural chemical compounds targeting the Keap1-NRF2 axis may have the potential for anti-SARS-CoV-2 therapy, such as andrographolide [ 60 ]. Bardoxolone and bardoxolone methyl, two NRF2 activators in clinical trials, showed their SARS-CoV-2 inhibition activity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, NRF2 activator SFN (phytochemical sulforaphane) has been reported to exhibit in vitro and in vivo antiviral activity against SARS-CoV-2 [ 59 ]. Some natural chemical compounds targeting the Keap1-NRF2 axis may have the potential for anti-SARS-CoV-2 therapy, such as andrographolide [ 60 ]. Bardoxolone and bardoxolone methyl, two NRF2 activators in clinical trials, showed their SARS-CoV-2 inhibition activity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The varying activities of these compounds and the absence or near absence of analogous activity amongst various stereo and other isomeric forms of them suggests that further tuning of the ribisin pharmacophore could provide compounds of even greater potency and, therefore, therapeutic utility as neuroprotectants. Furthermore, the very recent report [34] that certain compounds targeting the Keap1/Nrf2 axis can display potent anti‐SARS‐CoV‐2 activity means that the ribisins should be evaluated for their anti‐viral effects. Work directed toward such ends are now underway in our laboratories and results will be reported in due course.…”
Section: Discussionmentioning
confidence: 99%
“…[ 167 ] An eligible study demonstrated that a diterpenoid lactone and rographolide inhibits the interaction between Nrf2 and KEAP1, leading to the upregulation of Nrf2 expression. [ 239 ] Thus, and resveratrol could be effective against SARS‐CoV‐2 infection‐induced OS. [ 239 ] Due to the low bioavailability following oral administration, topical administration of the resveratrol through inhaled formulations could allow to achieve sufficiently high concentrations of the compound in the airways and to limit SARS‐CoV‐2 replication in Covid‐19 patients.…”
Section: Nrf2 In Covid‐19mentioning
confidence: 99%
“…[ 239 ] Thus, and resveratrol could be effective against SARS‐CoV‐2 infection‐induced OS. [ 239 ] Due to the low bioavailability following oral administration, topical administration of the resveratrol through inhaled formulations could allow to achieve sufficiently high concentrations of the compound in the airways and to limit SARS‐CoV‐2 replication in Covid‐19 patients. [ 240 ] Resveratrol preclinical research support further investigation resveratrol as a potential treatment of Covid‐19 and possibly other viral respiratory infections.…”
Section: Nrf2 In Covid‐19mentioning
confidence: 99%